Safety and efficacy of a feed additive consisting of l‐valine produced by Corynebacterium glutamicum CGMCC 18932 for all animal species (Xinjiang Fufeng Biotechnologies Co., Ltd.) - EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP); Vasileios Bampidis; Giovanna Azimonti; Maria de Lourdes Bastos; Henrik Christensen; Mojca Durjava; Birgit Dusemund; Maryline Kouba; Marta López‐Alonso; Secundino López Puente; Francesca Marcon; Baltasar Mayo; et al. (EFSA Journal)
Abstract Following a request from the European Commission, EFSA was asked to deliver a scientific opinion on the safety and efficacy of l‐valine produced by fermentation using a non‐genetically modified strain of Corynebacterium glutamicum (CGMCC 18932). l‐Valine is intended to be used in feed and water for drinking as a nutritional additive, functional group amino acids, their salts and analogues, for all animal species and categories. The production strain is considered suitable for the qualified presumption of safety (QPS) approach to safety assessment. The FEEDAP Panel concluded that l‐valine produced by C. glutamicum CGMCC 18932 is considered safe for the target species when supplemented to the diet in appropriate amounts according to the nutritional needs of the target species. The use of l‐valine produced using C. glutamicum CGMCC 18932 in animal nutrition is considered safe for the consumer and for the environment. No conclusion could be drawn on the potential of l‐valine produced using C. glutamicum CGMCC 18932 to be irritant to the skin or eyes, or a dermal sensitiser due to the lack of data. The FEEDAP Panel concluded that the l‐valine produced by fermentation using C. glutamicum CGMCC 18932 is an efficacious source of the essential amino acid l‐valine for non‐ruminant nutrition. To be as efficacious in ruminants as in non‐ruminants, supplemental l‐valine requires protection against ruminal degradation. The FEEDAP Panel expressed concerns on the use of amino acids in water for drinking for hygienic reasons.